Особенности управления персоналом в туристическом бизнесе Крыма - Болкунов, И.А. (Культура народов Причерноморья, 2013)
Рассмотрены особенности управления персоналом в туристическом бизнесе в условиях
нестабильного спроса. Для нестандартных формы найма персонала следует определить перечень
профессий, для которых такая форма занятости приемлема. Использование новых форм найма
позволяет сосредоточиться на управлении тем персоналом, который определяет качество
туристической услуги. Сезонность приводит к необходимости построения различных схем управления
персоналом для постоянных, условно-постоянных и временных (сезонных) сотрудников. У статті розглянуто особливості управління персоналом у туристичному бізнесі в умовах
нестабільного попиту. Для нестандартних форм найму персоналу слід визначити перелік професій, для
яких така форма зайнятості прийнятна. Використання нових форм найму персоналу дозволяє
зосередитися на управлінні тим персоналом, який визначає якість туристичної послуги. Сезонність
призводить до необхідності побудови різних схем управління персоналом для постійних, умовно-
постійних і тимчасових (сезонних) співробітників. In the article features of personnel management in the tourist business in uncertain demand
conditions have been considered. The clearly expressed seasonality of the activity leads to expansion of the
scope of the non-standard forms of employment and the use of contingent labor. With such flexible forms of
recruitment there should be identified the list of occupations for which this form of employment is acceptable,
reasonable, and will not reduce the quality of tourist services. In the case of contingent labor, the composition of
functions of personnel management is much narrower and requires less effort. New forms of recruitment allow
the personnel management service employees to focus on managing that staff that determines the quality of
tourist services. Seasonality complicates the classification of staff as a control object, leads to the need to build
different control schemes for permanent staff, conditional permanent and temporary (seasonal) employees. Each
control scheme has its own functional content. Those companies will benefit that will try to make each, even
temporary staff member part of a team, try to get them involved in corporate events and will be able to motivate
them. In this case, the company will be able to avoid the negative effects of seasonal and non-standard
recruitment.